2021
DOI: 10.1002/smll.202105682
|View full text |Cite
|
Sign up to set email alerts
|

Interface‐Induced Electrocatalytic Enhancement of CO2‐to‐Formate Conversion on Heterostructured Bismuth‐Based Catalysts

Abstract: greenhouse gas effect and to simultaneously convert CO 2 to value-added industrial products. [1][2][3][4][5] However, the inertness of CO 2 molecule, the sluggish multi-electron transfer kinetics, and the competitive hydrogen evolution reaction (HER) during CO 2 RR result in the high overpotential (η) to various degrees, which jeopardizes CO 2 RR performance. [6,7] Therefore, it is highly desirable to develop the electrocatalysts that are capable of compromising the above impediments and simultaneously achievi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 51 publications
0
56
0
Order By: Relevance
“…For instance, charge transfer at the interface between two different Bi-based materials led to optimizing the binding energy of adsorbates and lowered the thermodynamic energy barrier. 53,54 The effect of the semiconductor/cocatalyst interface on catalytic performance, however, has been rarely investigated even though there have been many reports of the PEC CO 2 RR to HCOOH by integrating photocathodes and cocatalysts (Table S2 †). Thermodynamically feasible production of HCOOH by Bi 2 O 3 -GaN binary system compared to each material of Bi 2 O 3 and GaN revealed that the design rule of heterogeneous catalysis can be applied to PEC reactions.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, charge transfer at the interface between two different Bi-based materials led to optimizing the binding energy of adsorbates and lowered the thermodynamic energy barrier. 53,54 The effect of the semiconductor/cocatalyst interface on catalytic performance, however, has been rarely investigated even though there have been many reports of the PEC CO 2 RR to HCOOH by integrating photocathodes and cocatalysts (Table S2 †). Thermodynamically feasible production of HCOOH by Bi 2 O 3 -GaN binary system compared to each material of Bi 2 O 3 and GaN revealed that the design rule of heterogeneous catalysis can be applied to PEC reactions.…”
Section: Resultsmentioning
confidence: 99%
“…(e) Long-term test and the corresponding FE COOH of Bi­(Te) 2 /NCNSs at −0.90 V (vs RHE). (f) Advanced Bi-based catalysts reported in recent years, FE HCOOH > 90% potential range and maximum j HCOOH in the potential range: Bi NS (ref ), Bi 2 S 3 –Bi 2 O 3 (ref ), Bi–Sn aerogel (ref ), Bi@Sn (ref ), N–Bi (ref ), Bi 2 O 3 NSs (ref ), and Bi-NC (ref ). Inset in (a): LSV curves of Bi­(Te) 2 /NCNSs in Ar-saturated and CO 2 -saturated KHCO 3 solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the previously reported Bi-based electrocatalysts those operated at the potential within −1.0 V in the H-type cell, the formate production rates in our study are competitive with much less synthesis time (Figure 3d; Table S4, Supporting Information). [16,20,26,27,34,39] Moreover, the GC-D/Bi exhibited a low Tafel slope of 99.8 mV dec -1 and outperformed TE-D/Bi (114.9 mV dec -1 ), illustrating the more favorable CO 2 RR kinetics on GC-D/Bi due to the incorporation of grain boundaries (Figure 3e). The electrochemical impedance spectroscopy (EIS) measurements in Figure S12 also imply a faster electron transfer rate on GC-D/Bi compared to that on TE-D/Bi.…”
Section: Co 2 Electrochemical Reduction Performancementioning
confidence: 99%